A manual guideline of building maintenance and management that can be implemented in STML building in UUM: A Path towards Sustainability - Lim, Chung Yean; Musa, Suria (Universiti Utara Malaysia, 2020)
This research paper assessed the building maintenance and management practices towards sustainability. The objective of this research is to understand the meaning of building maintenance and management towards sustainability. The second objective is to identify the types of building maintenance and management system. The third objective is to determine the solution to solve the issues regarding lack of level user’s awareness for building maintenance and management in STML building. The method of this research is by using qualitative approach, by involve the personal and telephonic interview session with the building maintenance and management’s students of STML. The findings of this research are the respondents reacting absolute positively towards the importance of building maintenance and management that can be implemented. As a result, a manual guideline is being carry out and the research that aims at immediate application were proven to be positive. However, a building maintenance manual should be provided for effective maintenance management and the life of building assets could be sustained.